2019
DOI: 10.5267/j.uscm.2019.5.001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing and innovative work behavior: The case of Vietnam

Abstract: Employees' knowledge sharing and innovative work behavior play an important role for the development of Vietnam telecommunication enterprises. Knowledge sharing along with two central processes; namely knowledge donation and collection, fosters employees' innovative work behavior of Vietnam telecommunication enterprises. Based on a sample size survey of 396 Vietnam telecommunication employees and exploration factor analysis (EFA), confirmatory factor analysis (CFA) and structural equation modeling (SEM), the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 53 publications
1
45
1
2
Order By: Relevance
“…Recently, there has been an increasing interest in examining the relationships between knowledge sharing and IWB (Nguyen et al , 2019; Akram et al , 2018; Hassan et al , 2018; Akhavan et al , 2015; Mura et al , 2013). For instance, a study conducted by Phung et al (2017) found that employee willingness to share their knowledge between one another enable the organization to promote IWB.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, there has been an increasing interest in examining the relationships between knowledge sharing and IWB (Nguyen et al , 2019; Akram et al , 2018; Hassan et al , 2018; Akhavan et al , 2015; Mura et al , 2013). For instance, a study conducted by Phung et al (2017) found that employee willingness to share their knowledge between one another enable the organization to promote IWB.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust is considered a cost-effective technique to enhance knowledge sharing within organizations (Dyer & Singh, 1998), and is believed to influence the knowledge sharing of people (Bulan & Sensuse, 2012), even in virtual teams or virtual communities (Chang & Chuang, 2011). It affects the processes of knowledge donating and collecting (Nguyen et al, 2019). Thus, we postulated that the more people trust others, the more people share knowledge with others.…”
Section: Trustmentioning
confidence: 99%
“…An organization's success is associated with workers' motivation and a strong desire to share knowledge with customers. Individuals may be motivated to share knowledge as they enjoy helping others (Alhawary et al, 2017;Nguyen, et al, 2019). Considering these views, it was hypothesized that: H2: Enjoyment in helping others has a positive relationship with knowledge sharing.…”
Section: Enjoyment In Helping Othersmentioning
confidence: 99%
See 2 more Smart Citations